Improvement of Physics Education as a Hallmark for Economic Growth and National Transformation in Nigeria - Mamedu, Anthony Imanche; Danjuma , Abubakar Isah; Barau, Abednego Moses; Adamu, Ahmed Rilwanu; Bawa, Yamusa Paul; Abatakula, Jarumi Yusuf; Bamaiyi, George Chindo (African Journal of Stability and Development (AJSD), 2024)
Physics can function in almost all works of life as its applications is found in medicine, engineering, finance, science, technology, and many other fields. And being useful in many areas of life implies that it has some contributions to make to development. Thus, there is the need for a nation that desires development and transformation to make Physics a basic requirement for the study of science and technology because of its positive contributions to the development of mankind. This paper highlights the need for quality Physics education as an essential instrument for economic growth and national transformation. Physics education enables scientists to learn important skills such as teamwork, networking, problem-solving skills, critical thinking, innovations, and self-discipline. These were highlighted to be vehicles that speed up the economic growth of a nation. Also, science, technology, business, and industry were stated to be areas that can bring about national development and transformation through quality physics education. The paper also highlighted the challenges of physics education that could hinder its exploits; it, therefore, suggested that students should be encouraged to apply lessons from physics to real life in a manner that would develop their skills.